Peran Sekolah Terhadap Kesehatan Mental Siswa Sekolah Dasar Selama Pandemi Covid-19 - Susanto, Eri (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2023)
Abstract This research was conducted to find out how the role of schools in overcoming students' mental health problems amid the COVID-19 pandemic, especially in primary education. This study uses scientific research methods based on qualitative research with literature studies. This research uses a literature study in Narrative Literature Review (NLR). This research cites research bases in print or online and from accredited scientific journals. The criteria for research sources, both in print and online and from scientific articles, describe mental health problems during the COVID-19 pandemic and have complete sections. The search method for the research base is using the Publish or Perish application which cites a database from Google Scholar using the keywords